Efficacy and Safety of Tracnil™ Administration in Patients with Dermatological Manifestations of PCOS: An Open-Label Single-Arm Study - Ezhil Arasan Ramanan; Sailatha Ravi; K. R. Radha Anbu; Margaret Michael (Dermatology Research and Practice)
Myo-inositol’s role in improving acne by reducing hyperandrogenism has been demonstrated in PCOS patients. Inositol and associated molecules display inhibitory properties against 5-α reductase, COX-2, and lipase enzymes in addition to their antimicrobial and anti-inflammatory properties. However, the role of myo-inositol is not well established in women patients with normal hormone levels but with clinical manifestations of PCOS. In this study, we evaluate the efficacy of Tracnil™, a combination of myo-inositol with folic acid and vitamin D3, in resolving acne in overweight women of menstruation age displaying normal hormone levels. It is a single-arm study conducted at 2 centers including 33 women with acne, hirsutism, and menstrual irregularities. Acne and hirsutism were assessed by manual lesion count, modified Cook’s scale, and modified Ferriman–Gallwey hirsutism score (mFGHS). Hormone levels and safety parameters were assessed throughout the study. Our results show that Tracnil™ monotherapy could drastically reduce acne-related lesions of both inflammatory and noninflammatory types as quickly as 8 weeks. Additionally, it improves hirsutism and menstrual irregularities. Adverse reactions were negligible during the whole study period with no drastic side effects reflected by a modulatory effect on hormone levels. Despite the subjects having normal hormone levels, the acne treatment with myo-inositol and vitamin D3 shows improvement in hirsutism and regularization of menstrual cycle. Therefore, we attribute the mechanism of action of Tracnil™ to modulation of receptor sensitivity to sex hormones or other downstream processing events. Tracnil™ may be considered as a first-line treatment for dermatological manifestations of PCOS even in the absence of significant hormonal abnormalities. This treatment is practically implementable in a dermatologists’s office practise.